Village Library Empowerment in an Effort to Increase Reading Interest in Children in Aman Damai Village, Sirapit District Langkat Regency - Siregar, Onan M; Selwendri (Talenta Publisher, 2023)
The low interest in children to read books is a problem that must be overcome by village apparatus in Aman Damai Village of Sirapit District. In addition, the management of the library is still very simple so that it is not able to attract the community, especially children to come, besides the lack of facilities and infrastructure. The purpose of providing solutions offered is to improve the administration and management system of village libraries in an effort to increase reading interest in children. This community service is addressed to the village apparatus as library manager and children. Methods used in achieving these goals include socialization to children and parents about the importance of reading interest in children and training in improving village apparatus skills in managing village libraries, providing books of various types such as textbooks to comic books for children. This community service is also done to train village apparatus in managing library through the provision of codes and numbers on books, drafting, to the lending system that can be done by children. The conclusion of this community service is that nowadays children visit the library more often because the available books can attract children’s interest to read. Moreover, the management and administration of library has become more organized than before.